2014
DOI: 10.1158/1541-7786.mcr-14-0106-t
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6–phosphatase Is a Key Metabolic Regulator of Glioblastoma Invasion

Abstract: Glioblastoma (GBM) remains the most aggressive primary brain cancer in adults. Similar to other cancers, GBM cells undergo metabolic reprogramming to promote proliferation and survival. Glycolytic inhibition is widely used to target such reprogramming. However, the stability of glycolytic inhibition in GBM remains unclear especially in a hypoxic tumor microenvironment. In this study, it was determined that glucose-6-phosphatase-α (G6PC/G6Pase) expression is elevated in GBM when compared to normal brain. Human-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 54 publications
2
70
0
Order By: Relevance
“…PTEN L320S -GFP, PTEN T277A -GFP, and PTEN delEx3 -GFP showed decreased activity to suppress cell migration, as measured by the Transwell (Fig. 1K) or 3-D nanopattern migration assays 2, 41, 42 (Fig. 1L).…”
Section: Resultsmentioning
confidence: 97%
“…PTEN L320S -GFP, PTEN T277A -GFP, and PTEN delEx3 -GFP showed decreased activity to suppress cell migration, as measured by the Transwell (Fig. 1K) or 3-D nanopattern migration assays 2, 41, 42 (Fig. 1L).…”
Section: Resultsmentioning
confidence: 97%
“…We therefore investigated the role of G6PC, a key enzyme in gluconeogenesis and glycogenolysis in OvCa [10]. We investigated a panel of glucose metabolism genes using TCGAOvCa dataset and found that G6PC was overexpressed in 17 % of cases, a frequency higher than that for most other genes related to glucose metabolism (Fig.…”
Section: G6pc Expression Was Increased In Ovca With Decreased Cdkn1b mentioning
confidence: 99%
“…One of the key enzymes that regulate glucose homeostasis and glycogenolysis is glucose-6-phosphatase, catalytic subunit (G6PC), which is located at the membrane of the endoplasmic reticulum [9]. Due to its physiologically important role in glycogenolysis and its critical tumourigenic role in glioblastoma [10], we hypothesize that G6PC plays critical roles in OvCa and that targeting it will commit OvCa to cell death.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that cancer stem cells from glioblastomas depend on G6PC and use the enzyme to counteract glycolytic inhibition (Abbadi et al, 2014). Interestingly, the knockdown of G6PC was able to decrease the aggressive phenotype of glioblastoma stem cells, potentially through the downregulation of the CD133/AKT pathway and an increase in glycogen accumulation through activation of GS and inhibition of glycogen phosphorylase, which has been previously shown to induce cancer cell death (Lee et al, 2004; Favaro et al, 2012).…”
Section: Gluconeogenesis Under Pathological Conditionsmentioning
confidence: 99%
“…Interestingly, the knockdown of G6PC was able to decrease the aggressive phenotype of glioblastoma stem cells, potentially through the downregulation of the CD133/AKT pathway and an increase in glycogen accumulation through activation of GS and inhibition of glycogen phosphorylase, which has been previously shown to induce cancer cell death (Lee et al, 2004; Favaro et al, 2012). G6PC knockdown also reduced migration, invasion, and cell viability (Abbadi et al, 2014). A number of studies have suggested that cancer cells have elevated levels of glycogen (Rousset et al, 1981), which is accumulated in response to hypoxic stimulation for later use in several cancer cell lines (Pelletier et al, 2012).…”
Section: Gluconeogenesis Under Pathological Conditionsmentioning
confidence: 99%